Wet Scrubber Performance Optimization Application Assisted with Electrochemical-Based Ammonia Sensors - Ikha Rasti Julia Sari; Januar Arif Fatkhurrahman; Bekti Marlena; Nani Harihastuti; Farida Crisnaningtyas; Yose Andriani; Nasuka Nasuka (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2019)
Crumb rubber is one of Indonesia’s agroindustry export commodities. This industry faces environmental problems due to their wastes, both liquid and air. The source of air pollution is commonly from drying process that emitted odor from its evaporation and heating phenomena. Industry uses wet scrubber technology as air pollution control from emitted odor from drying process. Preliminary identification in noncontrolled wet scrubber shown that wet scrubber efficiency around 47%. Low efficiency wet scrubbing process causes rain drop of water vapor around drying process. This research used electrochemical based sensor MICS 5524 as ammonia monitoring instrument, assisted with arduino as microcontroller to regulate water discharge through valve controlling scrubbing process. This electrochemical based sensor reads ammonia based on voltage reads by Arduino microcontroller. Ammonia reading then control scrubbing process by adjusting valve opening for spray water distribution. Wet scrubber efficiency increases to 66,96% due to water scrubbing control, also can save water utilization as high as 61,90%, followed by absence of rain drop contains ammonia around drying process area.